Financial Literacy, Investment Motivation, Information Technology, And Minimum Capital Affecting Generation Z Investment Interest in Purworejo Regency - Reyna Putri Gustyarni; Intan Puspitasari; Ishak Ishak (International Journal of Management Science and Information Technology, 2026)
The purpose of this study is to ascertain how financial literacy, investment motivation, information technology, and minimum capital affect Generation Z's inclination to invest in Purworejo Regency. Understanding the elements that influence Generation Z's intention to invest has become more important as their involvement in investment activities has grown. Information technology, minimum capital, financial literacy, and investing motivation are all thought to be significant factors that could affect investors' investment choices. This study used a structured questionnaire delivered using Google Forms as part of a quantitative research methodology. Purposive sampling was used to get data from 102 valid responses. Multiple linear regression was used to examine the collected data with the aid of SPSS software. The findings show that Generation Z's intention to invest is positively and significantly impacted by financial literacy, investment motivation, and minimal capital. In the meantime, investment intention is not significantly impacted by information technology. These results suggest that promoting investment intention among Generation Z requires enhancing financial awareness, boosting investment motivation, and expanding access to reasonably priced first investment money. Additionally, policymakers, financial institutions, and educational institutions can use the study's practical implications to develop initiatives that encourage youth investment engagement.